Curriculum for Sale: what is the wisdom? - Hamad, Bashir (Gezira Journal of Health Sciences, 2016)
Learning outcomes On completing the editorial, the reader is expected to: Define ‘curriculum’, curriculum type, name and model and the bought curriculum. Explain the pros and cons of the bought curriculum vies a vie locally produced curriculum.  Describe briefly the basic principles and process of modifying the bought curriculum. The title is not intended by any means to demote what we can call ‘the bought curriculum’ which, in recent years, has become the vogue, especially in the ‘rich’ developing countries, to an extent that it should earn  a place among the various types and models of medical (or rather health science) curricula. Another similar earner, which will not be our subject here, has the unfortunate model name of ‘the highbrid curriculum’.  It would be pertinent first to touch on some definitions of terms.